Bearing Fault Diagnosis in Electric Motors: the Example of Bahcesehir Natural Gas Electric Plant - (:unkn) unknown (KAUNAS UNIV TECHNOLOGY PRESS, 2009)
In this article, an experimental study based on the farsighted maintenance technology has been carried out on bearing fault development in asynchronous motors. The experimental studies have been carried out at a thermal power plant located in Istanbul-Esenyurt. The plant is a special-purpose company founded to implement the project of natural gas fired combined-cycle and cogeneration system having the capacity of 180 MW electricity and 180 MW heat. Esenyurt Power Plant has been developed to meet both the heat energy requirement of the region and electricity requirement of the country. The electric energy produced by the plant is transferred to the national network at 154 kV high-voltage line passing over the plant area. There are various induction motors in the power plant. Though the critical machines have stand-by units, any failures which may occur in the motors may cause workforce loss, time loss and economical losses. For that purpose, the bearing faults which may occur in the machines are detected at the start-Lip phase by making character inference of the vibration indications received from the motor regarding bearing faults; and by this way they can be replaced before they cause any failure in the machines.
Keywords: bearing fault diagnosis; fault detection; predictive maintenance